2014
DOI: 10.3758/s13423-014-0788-x
|View full text |Cite
|
Sign up to set email alerts
|

Selective interference of grasp and space representations with number magnitude and serial order processing

Abstract: It has been proposed that the metrics of space, time and other magnitudes relevant for action are coupled through a generalized magnitude system that also contribute to number representation. Several studies capitalized on stimulusresponse compatibility effects to show that numbers map onto left-right representations and grasp representations as a function of their magnitude. However, the tasks typically used do not allow disentangling magnitude from serial order processing. Here, we devised a working memory (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 31 publications
(33 reference statements)
0
13
0
Order By: Relevance
“…Specifically, numbers early within the instructed sequence are relatively associated with left, while later numbers in the instructed sequence are increasingly associated with right. This interaction between serial order in working memory and spatial processing has been replicated across numerous studies both at the level of response selection ( van Dijck and Fias, 2011 ; Ginsburg et al, 2014 ; Ginsburg and Gevers, 2015 ; van Dijck et al, 2015a ) and attentional orienting/selection (e.g., van Dijck et al, 2013 , 2014 ; De Belder et al, 2015 ), and has been demonstrated to occur in a similar way with non-numerical items (e.g., letters, pictures of objects) that need to be categorized according to a specific classification rule (e.g., van Dijck and Fias, 2011 ; van Dijck et al, 2014 ). Importantly, De Belder et al (2015) demonstrated an impact between space and ordinal position in working memory in the reversed direction, as exogenous lateral cues could facilitate retrieval from working memory when left and right cues were combined with retrieval of early and late items of the instructed sequence, respectively.…”
Section: Observations-to-be-explainedmentioning
confidence: 62%
“…Specifically, numbers early within the instructed sequence are relatively associated with left, while later numbers in the instructed sequence are increasingly associated with right. This interaction between serial order in working memory and spatial processing has been replicated across numerous studies both at the level of response selection ( van Dijck and Fias, 2011 ; Ginsburg et al, 2014 ; Ginsburg and Gevers, 2015 ; van Dijck et al, 2015a ) and attentional orienting/selection (e.g., van Dijck et al, 2013 , 2014 ; De Belder et al, 2015 ), and has been demonstrated to occur in a similar way with non-numerical items (e.g., letters, pictures of objects) that need to be categorized according to a specific classification rule (e.g., van Dijck and Fias, 2011 ; van Dijck et al, 2014 ). Importantly, De Belder et al (2015) demonstrated an impact between space and ordinal position in working memory in the reversed direction, as exogenous lateral cues could facilitate retrieval from working memory when left and right cues were combined with retrieval of early and late items of the instructed sequence, respectively.…”
Section: Observations-to-be-explainedmentioning
confidence: 62%
“…In these models, order is coded through positional tags associated to each item. Even if no consensus has emerged concerning the actual nature of the positional tags, recent work on spatialization (e.g., Ginsburg et al, 2017;Guida, Carnet, et al, 2018;Guida, Leroux, et al, 2016;Rinaldi et al, 2015;van Dijck, Fias, & Andres, 2015) has showed that their nature could be spatial (see also Rinaldi, Merabet, Vecchi, & Cattaneo, 2018), like in the mental slotted line we are proposing.…”
Section: Slotted Schemas: the Spoarc Effectmentioning
confidence: 96%
“…This indicates that some aspects of basic motor control involve high-order cognitive processes. Importantly, as compared to previous studies (Glover et al, 2004 ; Voelcker-Rehage and Alberts, 2007 ; Voelcker-Rehage et al, 2006 ; Li et al, 2009 ; Hesse and Deubel, 2011 ; Guillery et al, 2013 ; Behmer and Fournier, 2014 ; Bumsuk et al, 2014 ; Kawagoe and Sekiyama, 2014 ; Quak et al, 2014 ; Spiegel et al, 2014 ; Korotkevich et al, 2015 ; Maes et al, 2015 ; van Dijck et al, 2015 ), the performance of the cognitive tasks used in the present study did not involve any explicit motor function. For this reason, the cognitive-motor interaction observed in the present study cannot be due to competition for resources specifically involved in motor control.…”
Section: Discussionmentioning
confidence: 99%
“…If the two tasks interfere with each other when performed simultaneously, it is assumed that both tasks share similar resources and processing abilities. Accordingly, recent studies have shown that performing a high-order cognitive task may interfere with the realization of upper limb movements such as reaching and grasping (Li et al, 2009 ; Spiegel et al, 2013 , 2014 ; Gunduz Can et al, 2017 ), precision grip-lift (Guillery et al, 2013 ; Bumsuk et al, 2014 ), precision and power grip squeezing (van Dijck et al, 2015 ), force tracking (Au and Keir, 2007 ; Voelcker-Rehage et al, 2006 ; Mehta and Agnew, 2011 ; Temprado et al, 2015 ), and tapping (Serrien, 2009 ; Fraser et al, 2010 ; Korotkevich et al, 2015 ). These studies suggest that habitual dexterous manipulation may not only rely entirely on automatic processes and, instead, may involve or interact with higher-order cognitive functions to be planned and executed.…”
Section: Introductionmentioning
confidence: 99%